Understory plant species and community changes following a mountain pine beetle outbreak in Rocky Mountain National Park, USA. (10th March 2022) - Pappas, Gregory S.; Tinker, Daniel B.; Rocca, Monique E.
Abstract: Aims: The response of understory plants is an important, yet understudied element of forest dynamics associated with mountain pine beetle (MPB) disturbance. Here, we provide a detailed assessment of both the changes in understory species and communities over a 5‐year period following severe MPB‐induced lodgepole pine mortality. Specifically, we examine species turnover, rarity and mobility over time, and evaluate shifts in community composition, including the potential for post‐outbreak community homogenization or differentiation. Location: Western Rocky Mountain National Park in the southern Rocky Mountains, Colorado. Methods: We collected species occurrence data across lodgepole pine‐dominated forest understories using repeated sampling of the same study sites (during the peak of MPB activity and 5 years after). Results: More species appeared than disappeared 5 years after the peak of the outbreak. New species were comprised of both early‐ and late‐successional species, suggesting the presence of rather high microhabitat heterogeneity. Although most species remained relatively rare, the number of exceedingly rare species decreased, and the number of highly common species increased. Several species were able to take advantage of the new stand conditions and expand throughout the study area. Some species appeared to spread locally over short distances mainly via vegetative reproduction, others expanded primarily upwards in elevation, probably through long‐distance dispersal and some spread over both short and long distances. Non‐native species doubled in occurrence and tended to spread upslope, towards the interior of the park, yet remained a small component of the understory overall. Shifts in community composition were minimal, but a slight convergence of plant community groups suggests a trend towards community homogenization. Conclusions: Our results demonstrate that even relatively sparse and depauperate lodgepole pine forest understories may be altered in diverse ways following MPB‐induced overstory mortality, depending on the unique ability of species to respond to changes in site conditions and resource availability. Abstract : Five years after a severe mountain pine beetle outbreak in lodgepole pine‐dominated forests, several understory plant species were able to take advantage of heterogeneous conditions and expand over short and/or long distances. Most ascended in elevation, including non‐natives, which doubled in occurrence. Although changes in community composition were minimal, a convergence of species groups indicates a trend towards community homogenization.